Participatory-based management of village-owned enterprises to optimize village original revenue: A case study of Tridadi Makmur, Sleman, Indonesia - Murtodo, M.; Fauziah, Puji Yanti (Universitas Muhammadiyah Malang, 2026)
Village-owned enterprises have been positioned as strategic instruments for strengthening local economic autonomy, yet many village enterprises in Indonesia still struggle to contribute meaningfully to village original revenue. This study examining how participatory-based management was implemented in BUM Kalurahan Tridadi Makmur, Sleman, and how such management supported the optimization of village original revenue. A descriptive qualitative approach was employed. Data were collected through in-depth interviews, observation, and documentation involving the enterprise director, supervisory board, village head, and members of the village consultative body. Data were analyzed using the Miles et al interactive model comprising data collection, condensation, display, and conclusion drawing. The findings show that effective management was built through four interrelated functions: participatory planning, adaptive organizing, business-oriented implementation, and continuous supervision. Community participation appeared not only in deliberative forums but also in labor involvement and capital participation. Quantitative institutional records indicate strong business growth from 2023 to 2024, including a 37% increase in total assets, a 30% increase in gross income, and a 541% increase in net income. However, annual transfers from the enterprise to village revenue fluctuated across 2018-2024, indicating that financial contribution depends on wider operational and strategic considerations, not merely business expansion. The major supporting factors were village government support, leadership, community participation, and pentahelix collaboration, whereas human-resource constraints and increasing business competition remained key obstacles. The article contributes an empirically grounded management model for strengthening village enterprises and supports SDG 8 by demonstrating how locally managed enterprises can expand productive employment and inclusive rural economic growth.